Reconstructing The Authority of Customary Villages in the Governance of Culture-Based Tourism in Bali Through the Perspectives of Legal Pluralism and Collaborative Governance - I Dewa Gede Herman Yudiawan; Si Ngurah Ardhya; Ni Luh Wayan Yasmiati; Dewa Gede Sudika Mangku (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
This study examines the reconstruction of the authority of desa adat in the implementation of culture-based tourism in Bali from the perspectives of legal pluralism and collaborative governance. The research is motivated by the normative recognition of desa adat within regional regulations, which, however, has not been fully followed by substantive authority in managing tourism activities. This condition gives rise to overlapping authorities, weak institutional coordination, and limited community participation in tourism governance. Employing a qualitative research method with a normative and socio-legal approach, this study analyzes legal frameworks, institutional practices, and the role of local wisdom in tourism development. The findings reveal that the coexistence of state law and customary law has not been optimally harmonized, resulting in the marginalization of desa adat in strategic decision-making processes. In addition, the absence of an effective collaborative governance model further weakens the capacity of desa adat to manage tourism sustainably. Therefore, this study proposes a reconstruction model that strengthens the legal authority, institutional capacity, and collaborative role of desa adat. This reconstruction integrates the values of Tri Hita Karana, optimizes local economic institutions, and promotes participatory governance. The study concludes that empowering desa adat as a central actor in tourism governance is essential for achieving sustainable, culturally rooted, and community-based tourism development in Bali.